Searching for Iris - Bryson, Teresa (East Carolina University, 2017)
Iris Jones, a recent college graduate and intern at the Museum of History in Wilmington, North Carolina, discovers a reference to a German U-Boat off the coast of Wilmington during WWII while sorting through donations to the museum. The reference, which is in a diary, contains little information, only two names and a vague description of the location. However, after sorting and cataloging more donations, Iris finds a letter to the writer of the diary and learns enough to find the owner of the diary. With help from Nico, Iris's brother, she finds the owner of the diary. However, Iris's search for the German U-Boat is put on hold when she is put in charge of part of the museum's new WWII exhibit. While working on the exhibit, Iris collects flight and captains' logs in the hope of finding more information on the U-Boat. After reading several logs, Iris finds more information on the U-Boat, including coordinates for where it was sighted. With help from Nico, Iris maps the possible path of the U-Boat and creates a search grid. After several weeks of searching and interference from Liz, one of Iris's coworkers, she finds the U-Boat.
Keywords: North Carolina; Submarines (Ships)--North Carolina--Fiction